Broadband near-IR absorbing Au-dithiolene complexes bearing redox-active oligothiophene ligands. Issue 1 (21st November 2018) - Wright, Iain A.; Wilson, Claire; Coles, Simon J.; Skabara, Peter J.
Abstract : Oligothiophene chains bound to metal dithiolene centres display hybrid optoelectronic properties including tunable energy levels and broadband absorption across the visible spectrum. Abstract : A series of three homoleptic, monoanionic gold dithiolene complexes of oligothiophene ligands which coordinate via a central thiophene-3, 4-dithiolate chelate are presented. The oligomer chains are three, five and seven thiophenes long and the complexes display hybrid optoelectronic properties featuring characteristics of both the oligothiophene chains and the delocalised metal dithiolene centre. The properties of the complexes have been characterised using a variety of spectroscopic and electrochemical methods complemented by computational studies. Solid state spectroelectrochemistry has revealed that upon oxidation these complexes display intense and broad absorption across the visible spectrum. In attempting to produce nickel analogues of these materials a single crystal of a photo-oxidised nickel dithiolene complex has also been isolated.